Evidence-based software engineering: systematic literature review process based on visual text mining - Scannavino, Katia Romero Felizardo (2012)
Context: Systematic literature review (SLR) is a methodology used to aggregate all relevant evidence of a specific research question. One of the activities associated with the SLR process is the selection of primary studies. The process used to select primary studies can be arduous, particularly when the researcher faces large volumes of primary studies. Another activity associated with an SLR is the presentation of results of the primary studies that meet the SLR purpose. The results are generally summarized in tables and an alternative to reduce the time consumed to understand the data is the use of graphic representations. Systematic mapping (SM) is a more open form of SLR used to build a classification and categorization scheme of a field of interest. The categorization and classification activities in SM are not trivial tasks, since they require manual effort and domain of knowledge by reviewers to achieve adequate results. Although clearly crucial, both SLR and SM processes are time-consuming and most activities are manually conducted. Objective: The aim of this research is to use Visual Text Mining (VTM) to support different activities of SLR and SM processes, e.g., support the selection of primary studies, the presentation of results of an SLR and the categorization and classification of an SM. Method: Extensions to the SLR and SM processes based on VTM were proposed. A series of case studies were conducted to demonstrate the usefulness of the VTM techniques in the selection, review, presentation of results and categorization context. Results: The findings have showed that the application of VTM is promising in terms of providing positive support to the study selection activity and that visual representations of SLR data have led to a reduction in the time taken for their analysis, with no loss of data comprehensibility. The application of VTM is relevant also in the context of SM. Conclusions: VTM techniques can be successfully employed to assist the SLR and SM processes